VOLCANIC SOURCE FOR FIXED NITROGEN IN THE EARLY EARTH'S ATMOSPHERE - Mather T.A.; Pyle D.M.; Allen A.G. (My University, 2004)
Hot volcanic vents promote the thermal fixation of atmospheric N2 into biologically available forms. The importance of this process for the global nitrogen cycle is poorly understood. At Masaya volcano, Nicaragua, NO and NO2 are intimately associated with volcanic aerosol, such that NOx levels reach as much as an order of magnitude above local background. In-plume HNO3 concentrations are elevated above background to an even greater extent (≤50 μmol·m-3). We estimate the production efficiency of fixed nitrogen at hot vents to be ˜3 × 10-8 mol·J-1, implying present-day global production of ˜109 mol of fixed N per year. Although conversion efficiency would have been lower in a preoxygenated atmosphere, we suggest that subaerial volcanoes potentially constituted an important source of fixed nitrogen in the early Earth, producing as much as ˜1011 mol·yr-1 of fixed N during major episodes of volcanism. These fluxes are comparable to estimated nitrogen-fixation rates in the prebiotic Earth from other major sources such as bolide impacts and thunderstorm and volcanic lightning.
Keywords: nitrogen cycle; volcanic gases; Masaya volcano (Nicaragua); atmospheric evolution